Modelling external short circuit behaviours of fresh and degraded lithium-ion batteries - Zhou,Y; Lukow,K; Bonkile,MP; Wu,B (Journal of Energy Storage, 2026)
Improving the safety characteristics of lithium-ion batteries is essential for mass adoption of the technology, with external short circuit (ESC) tests being one of the most common benchmarks. These tests are most commonly applied at beginning-of-life (BOL), however, significant knowledge gaps remain regarding how the physics of ESCs evolve with cell ageing. In this study, we simulate the ESC behaviour from BOL to 1000 full cycles. At BOL, we identify two regimes of behaviour for the ESC current, an initially high but rapidly decreasing current phase, and a lower quasi-steady state current phase. The initial phase is characterised by the low but emerging overpotential, whilst the latter phase is defined by depletion of lithium-ions in the cathode-domain electrolyte phase and diffusion limitations. When ESC initial conditions are varied across state-of-charge (SOC) and initial cell/ambient temperatures, higher SOC and initial cell/ambient temperatures both result in more severe ESC behaviour due to higher voltage driving forces and lower overpotentials respectively. As the cell is degraded in a solid-electrolyte interphase growth dominated regime, the increased cell resistance, reduces the severity of the ESC across all conditions, with the 2-phase ESC current behaviour suppressed due to the lower current. We map these behaviours across a range of conditions providing indicative safety maps and underpinning insight into ESC behaviour from BOL towards aged states.